Sulfonic acid functionalized mesoporous silicas and organosilicas: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Srilakshmi, Ch.; Parischa, Renu; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
Ethane bridged mesoporous organosilicas and MCM-41 having sulfonic acid groups in the pore channels were prepared by co-condensation method as well as grafting method, using 3-mercaptopropyltriethoxysilane (3-MPTS) as the sulfur precursor. TEM and N-2 sorption isotherm analysis revealed that the mesoporous structural ordering is retained after the functionalization and modifications of organic groups while FT-IR, Raman, XPS and solid-state C-13 CP MAS NMR shows the presence of sulfonic acid groups and the stability of the mesoporous framework. The catalytic activity of the developed materials was evaluated in the liquid phase Claisen-Schmidt condensation reaction of acetophenone with benzaldehyde, to probe the effect of mesoporous support surfaces as well as the role of preparation methods. Results showed that sulfonic acid functionalized ethane-silica samples were more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: condensation; ethane-silica; heterogeneity; sulfonic acids

On the influence of spatial heterogeneity on an internal boundary layer at a short fetch - Murthy, B. S.; Latha, R.; Sukumaran, Cini; Shivaji, A.; Sivaramakrishnan, S. (Journal of Earth System Science, 2009)
Surface layer meteorological data collected at a coastal site, at Vasco-Da-Gama (15A degrees 21'N, 73A degrees 51'E, 58.5m MSL) (13-18 July, 2002) with prevailing southwesterly surface winds are analyzed to study the characteristics of internal boundary layer at a short fetch using an instrumented tower (9 m). The spectral and turbulence characteristics of wind are compared with earlier measurements made at a comparatively homogeneous terrain and the standards available in literature. The study show the smaller eddies in the vertical velocity spectrum attains equilibrium with the underlying surface at a short fetch itself and follows spectral similarity. However, this is not followed by longitudinal and transverse velocity spectra under unstable as well as stable conditions.
Keywords: heterogeneity; IBL; sea-land interface; wind spectra